Pemberdayaan Ekonomi Masyarakat Melalui Pengolahan Minyak Jelantah Pada Komunitas Fatayat Nahdlatul Ulama Candirenggo Singosari - Abdul Bashith; Saiful Amin; Puji Endah Purnamasari; Muchammad Akbar Kurniawan; Lailatul Fa’izah (Jurnal Pemberdayaan Masyarakat, 2024)
Waste cooking oil that is disposed of carelessly has an impact on environmental degradation. Based on a survey that has been conducted, the problems faced by partners are 1) the community, especially Candirenggo Village, does not know and understand much about the processing of used cooking oil. 2) Not many parties have conducted training in processing used cooking oil, especially for the Fatayat NU community. This service aims to provide counselling and training related to the processing of used cooking oil or used cooking oil for the Fatayat NU Candirenggo community. This community service activity using the Asset Based Community Development (ABCD) method is described in a cycle consisting of the preparation stage, implementation stage, and monitoring and evaluation stage. This community service activity was carried out from March to August 2024 in Candirenggo Singosari Village, Malang Regency. The community, especially members of the Fatayat NU community in Candirenggo Village RT 05 RW 05 Singosari became the target audience for this community service. Used cooking oil waste management training activities have shown to be very effective in increasing community awareness and skills in protecting the environment. Through this training, members of Fatayat NU Candirenggo are equipped with knowledge and practical skills to manage used cooking oil waste into value-added products, such as soap and aromatherapy candles. This activity not only supports environmental conservation efforts but also improves the welfare and economic independence of community members.